2009
DOI: 10.1530/eje-08-0797
|View full text |Cite
|
Sign up to set email alerts
|

Studies of insulin resistance in patients with clinical and subclinical hypothyroidism

Abstract: Objective: Although clinical hypothyroidism (HO) is associated with insulin resistance, there is no information on insulin action in subclinical hypothyroidism (SHO). Design and methods: To investigate this, we assessed the sensitivity of glucose metabolism to insulin both in vivo (by an oral glucose tolerance test) and in vitro (by measuring insulin-stimulated rates of glucose transport in isolated monocytes with flow cytometry) in 21 euthyroid subjects (EU), 12 patients with HO, and 13 patients with SHO. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
277
2
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(338 citation statements)
references
References 27 publications
20
277
2
18
Order By: Relevance
“…Moreover, monocytes express all GLUT isoforms found in muscle and adipose tissue, and the increases in glucose transport in response to insulin in these cells correspond well with those observed in tissues quantitatively important for glucose disposal (15,19). We have previously used monocytes as a cellular model to study insulin sensitivity (11,15); furthermore, we have suggested the important role of GLUT3 in compensating increased tissue demand for glucose in the HR state (20,21).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, monocytes express all GLUT isoforms found in muscle and adipose tissue, and the increases in glucose transport in response to insulin in these cells correspond well with those observed in tissues quantitatively important for glucose disposal (15,19). We have previously used monocytes as a cellular model to study insulin sensitivity (11,15); furthermore, we have suggested the important role of GLUT3 in compensating increased tissue demand for glucose in the HR state (20,21).…”
Section: Discussionsupporting
confidence: 55%
“…Some of the EU volunteers of the present study were used in a similar study published recently by our group (11). The protocol was approved by the hospital ethics committee, and subjects gave informed consent.…”
Section: Subjectsmentioning
confidence: 99%
“…Львівський національний медичний університет імені Данила Галицького, Львів ÂÑÒÓÏ Äîñë³äaeåííÿ îñòàíí³õ ðîê³â âñòàíîâèëè íàÿâí³ñòü ³íñóë³íîðåçèñòåíòíîñò³ ó õâîðèõ íà ã³-ïîòèðåîç [10]. Ç'ÿâèëèñÿ íàóêîâ³ ïðàö³, ùî çà-ïî÷àòêóâàëè âèâ÷åííÿ âïëèâó ³íñóë³íîâèõ ñåí-ñèòàéçåð³â íà òèðåî¿äíèé ñòàòóñ, ïîêàçíèêè âóãëåâîäíîãî òà ë³ï³äíîãî îáì³íó ó õâîðèõ ç ³í-ñóë³íîðåçèñòåíòí³ñòþ òà ñóáêë³í³÷íèì àáî êë³-í³÷íèì ã³ïîòèðåîçîì ³ç öóêðîâèì ä³àáåòîì (ÖÄ) àáî áåç íüîãî [6,8,10].…”
Section: метаболічний вплив метформіну та піоглітазону на тиреоїдний unclassified
“…Ç'ÿâèëèñÿ íàóêîâ³ ïðàö³, ùî çà-ïî÷àòêóâàëè âèâ÷åííÿ âïëèâó ³íñóë³íîâèõ ñåí-ñèòàéçåð³â íà òèðåî¿äíèé ñòàòóñ, ïîêàçíèêè âóãëåâîäíîãî òà ë³ï³äíîãî îáì³íó ó õâîðèõ ç ³í-ñóë³íîðåçèñòåíòí³ñòþ òà ñóáêë³í³÷íèì àáî êë³-í³÷íèì ã³ïîòèðåîçîì ³ç öóêðîâèì ä³àáåòîì (ÖÄ) àáî áåç íüîãî [6,8,10].…”
Section: метаболічний вплив метформіну та піоглітазону на тиреоїдний unclassified
“…The association between thyroid function and body weight in euthyroid individuals has been given an important medical concern. The overt hypothyroidism (OH) and sub-clinical hypothyroidism (SCH) are established risk factors for insulin resistance [2,3] and multiple studies have proved the association between insulin resistance, hypothyroidism and metabolic syndrome for overt hypothyroidism [4][5][6][7]. The prevalence of thyroid disease in patients with diabetes is significantly higher than that in the general population [8].…”
Section: Introductionmentioning
confidence: 99%